Nyelonding sebagai Instrumen Pembangunan Sosial: Model Pemberdayaan Generasi Muda Berbasis Seni Tradisional di Desa Adat Bayad, Kabupaten Gianyar Bali - Ni Made Aristya Dianti; Anak Agung Ayu Arun Suwi Arianty; Luh Eka Susanti; Ida Bagus Soma Antara; Putu Sri Damayanti; Made Widya Paramitha (Abdimas Indonesian Journal, 2026)
The digital era has changed the way young people interact with others. Many young people tend to be more individualistic and show less concern for their social environment. This condition has led to lower participation and weakened social capital in rural communities. This community service activity aims to empower young people through nyelonding activities as an instrument to strengthen social capital in the digital era. The program was carried out using a participatory approach, including initial observation, the formation of a Selonding music group, regular training sessions, and continuous assistance. The participants were village youths who were previously less active in social and cultural activities. The results show improvements in discipline, teamwork, responsibility, and self-confidence among the participants. In addition, nyelonding activities helped strengthen social relationships and increased care for the surrounding community. These findings indicate that traditional arts can be an effective medium for youth empowerment and social capital strengthening, while also contributing to the preservation of local culture in the digital era.